Gambaran Tingkat Pengetahuan Tentang Menyikat Gigi Pada Siswa Kelas VII SMPN 1 Kebonagung Pacitan - Dhea Aulia Hapsari; Siti Sulastri; Almujadi Almujadi (Poltekkes Kemenkes Yogyakarta, 2017)
Knowledge comes from experience through sensory perception. Knowledge is obtained by some factors such as education level, jobs, age, socio-economics, experiences, cultures, environments, and information. In the community, lack of knowledge causes wrong behavior in brushing their teeth. Brushing teeth is one of the procedures to keep mouth and teeth healthy. This study aimed to describe 7thgrade students of Junior High School (JHS) 1 Kebonagung Pacitan’s knowledge about brushing teeth. This Study was descriptive research with cross-sectional design. The subjects were all of the 7th-grade students of JHS 1 Kebonagung Pacitan (56 students). The result showed that respondents with adequate knowledge were 10 (17.9%), respondents with moderate knowledge were 26 (46.4%) with most of them were female, and respondents with inadequate of knowledge were 20 (35.7%). Based on the result, the conclusion was the knowledge about brushing teeth of 7th-grade students of JHS 1 Kebonagung Pacitan was moderate (46.4%).